2021
DOI: 10.3390/diagnostics11020334
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of 68Ga DOTA-TATE PET/CT, 111In-Pentetreotide SPECT/CT and CT for Diagnostic Workup of Neuroendocrine Tumors

Abstract: Neuroendocrine tumors (NETs) are relatively rare neoplasms arising from the hormone-producing neuroendocrine system that can occur in various organs such as pancreas, small bowel, stomach and lung. As the majority of these tumors express somatostatin receptors (SSR) on their cell membrane, utilization of SSR analogs in nuclear medicine is a promising, but relatively costly approach for detection and localization. The aim of this study was to analyze the cost-effectiveness of 68Ga-DOTA-TATE PET/CT (Gallium-68 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
18
0
2
Order By: Relevance
“…Even if the cost-effectiveness of PET imaging in neuroendocrine neoplasms was not evaluated by specific meta-analyses, a recent study comparing 68 Ga-SSA PET/CT, SSR SPECT/CT and CT underlined that the use of 68 Ga-SSA PET/CT in NETs is cost-effective. The additional costs of 68 Ga-SSA PET/CT, when compared to CT alone, are justified in the light of potential savings in therapy costs and better outcomes [51].…”
mentioning
confidence: 99%
“…Even if the cost-effectiveness of PET imaging in neuroendocrine neoplasms was not evaluated by specific meta-analyses, a recent study comparing 68 Ga-SSA PET/CT, SSR SPECT/CT and CT underlined that the use of 68 Ga-SSA PET/CT in NETs is cost-effective. The additional costs of 68 Ga-SSA PET/CT, when compared to CT alone, are justified in the light of potential savings in therapy costs and better outcomes [51].…”
mentioning
confidence: 99%
“…F, The cost of detecting a recurrence was $22% higher in the SoC evaluated cohort ($USD57,250) than the NETest cohort ($USD44,600). 12,13,25 þNETest indicates follow-up strategy that utilizes a POD30 NETest-based stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported that new imaging tracers targeting cell surface molecules such as Ga 68 -PSMA or Ga 68 -DOTATATE PET might improve cost effectiveness ( 63 65 ), whereas product cost themselves are relatively expensive. OX40 immunoPET might be expensive compared with standard examinations in the clinic.…”
Section: Discussionmentioning
confidence: 99%